Ethical Principles in the Face of the Main Chromosomal Pathologies (Global Journal of Medical Research, 2020)
Belonging to a health profession requires an understanding of the ethical problems faced by its members. Chromosomal pathologies are very rare among live births; which does not give them priority for public health in developing countries, however these pathologies exist and can affect any family. The present study first describes patients with chromosomal pathologies in the population of western Algeria. The second step proposes to think about applying ethical principles to the practice of cytogenetics. We carried out a study by a triangulation of the sources of information: The study of files, the prospection in the international bioethical literature and the research in the authorized texts as well as the international instruments. This type of approach makes it possible to reflect on the border between ethics and law. Ethical reflection on this subject therefore appears essential to attract attention to these patients in order to give them a better place in our society.
Keywords: ethics; chromosome anomalies; chromosome pathologies; cytogenetics